Low genetic variation of foliar traits among Prosopis chilensis (Leguminosae) provenances - Bessega, Cecilia Fabiana (2022)
Prosopis chilensis (Molina) Stuntz (Leguminosae) is a valuable native species in Argentina that has been proposed to be used in reforestation, afforestation and restoration programmes. Natural provenances show important differentiation in height, shape, spine size, fruits and foliar traits throughout their distribution in the semiarid Monte ecoregion. The goal of this work was to characterize the genetic basis of the leaf variation in P. chilensis aiming to contribute to the improvement management program. We analyzed morphological variation and estimate narrow sense heritability for ten quantitative traits from a provenance-progeny trial founded from open pollinated families. We assessed the variance components by a generalized linear mixed model. Differences among provenances were quantified through univariate QST statistics and multivariate discriminant analysis of principal components. Finally, univariate and multivariate neutrality test were conducted to unveil the evolutionary forces that shape the variation. Univariate and multivariate analysis showed low genetic variation in foliar traits among provenances grown in the common garden. Consistently, the QST estimates for each trait were low. Both, the univariate (QST–FST comparison) and the multivariate neutrality test suggest that the leaf variation among provenances may be shaped by genetic drift rather than selective forces. Heritability estimates were significant only for leaflet apex and leaflet apex/leaflet area. Since genetic variation for most foliar traits among provenances estimated under controlled environmental conditions were very low or absent, the variation described in the wild would be explained merely by plastic response to varying environments. These results are discussed in terms of adaptive strategies and the use of different provenances as seed sources within the framework of the improvement program. It is expected that P. chilensis seeds or seedlings from trees selected under economical criteria will be able to develop in different areas thanks to the phenotypic plasticity of leaf traits.